Financiamento eleitoral: disputas e estratégias em torno da votação e aplicação do Fundo Especial de Financiamento de Campanhas (FEFC) - Silva, Nathália Letícia de Pina (2021)
The present research aims to understand the incentives that defined the voting and distribution strategies of the Special Fund for Campaign Financing. The general objective of the research was to analyze the voting process for implementing the Electoral Fund and the party strategies for its distribution in the 2018 general elections. electoral campaigns that were approaching, we tried to understand if 1) the volume of resources for each political party determined the vote of parliamentarians; and whether 2) the dispute for majority positions was concentrated in parties with the greatest funding from the FEFC. In this way, we seek to answer the following question: What incentives defined the FEFC voting and distribution strategies? The specific objectives that guide this research consist of: 1) Identifying the changes in Law No. 9,504/97 that affected the 2018 electoral process, especially with regard to articles dealing with campaign financing; 2) analyze the political disputes in both National Chambers around the vote for the creation of the FEFC; 3) understand to what extent the changes impacted party resource distribution strategies; 4) analyze the accountability of parties that had candidates for the 2018 election. For this, we propose a comparative analysis, combined with the rational choice neo-institutionalism approach to investigate the motivations and reorganization of political parties in this electoral process. In addition, we will carry out a qualitative analysis of the voting speeches of the project that culminated in Law No. 13.487/2017 and a quantitative analysis of the party's accountability (expenses) in the 2018 election.